Induction of Somatic Embryos in Cultured Leaf Explants of Coffea Arabica - E. Noerhadi; T. Yasuda; Arbayah Siregar; Risco G. Budji (Institute for Research and Community Services (LPPM) ITB, 1985)
Sari. Tulisan ini menguraikan induksi embrio somatik dan pertumbuhan planlet yang dihasilkan dari kultur jaringan daun Coffea arabica. Untuk pembentukan kalus, potongan jaringan daun ditanam pada medium Linsmaier dan Skoog dengan 3% sukrosa ditambah berbagai konsentrasi 2,4-asam diklorofenoksi asetat atau asam naftalen asetat dan kinetin. Delapan belas minggu setelah penanaman, kalus akan dibentuk pada medium Linsmaier dan Skoog dengan 2 pM 2,4-asam diklorofenoksi asetat dan 5-7 pM kinetin dan juga pada medium dengan 0,05 pM asam naftalen asetat dan 6-8 pM kinetin. Pembentukan embrio somatic diperoleh dengan pemotongan kalus pada medium padat Linsmaier dan Skoog dengan 3 pM sampai 35 pM kinetin dan 0,05 pM asam indole butirat dan juga dalam medium cair Gamborg, Miller, dan Ojima yang diberi 0,05 pM sampai 2,5 pM 2,4-asam diklorofenoksi asetat. Abstract. Somatic embryo induction and subsequent plantlets development in culture of Coffea arabica leaf tissue explants was described. For callus formation leaf segments were grown on medium Linsmaier and Skoog with 3% sucrose and varying concentrations of 2,4-Dichlorophenoxyaceticacid or Naphthalene Acetic Acid and Kinetin. Eighteen weeks after inoculation, callus will be formed on Linsmaier and Skoog's medium with 2 Î¼M 2,4-Dichlorophenoxyacetic acid and 5-7 Î¼M Kinetin and also on medium with 0.05 Î¼M Naphtalene Acetic Acid and 6-8 Î¼M Kinetin. Somatic embryos are then formed by inoculation of calli segments on medium Linsmaier & Skoog with 3 Î¼M to 35 Î¼M Kinetin and 0.05 Î¼M Indole Butyric Acid. Somatic embryos are also formed in liquid medium of Gamborg, Miller and Ojima supplemented with 0.05 Î¼M to 2.5 Î¼M 2,4-Dichlorophenoxyacetic acid.